Genomic and metabolomic insights into the natural product biosynthetic diversity of a feral-hog-associated Brevibacillus laterosporus strain. - Christine M Theodore; Blake W Stamps; Jarrod B King; Lauren S L Price; Douglas R Powell; Bradley S Stevenson; Robert H Cichewicz (PLoS ONE)
Bacteria associated with mammals are a rich source of microbial biodiversity; however, little is known concerning the abilities of these microbes to generate secondary metabolites. This report focuses on a bacterium isolated from the ear of a feral hog from southwestern Oklahoma, USA. The bacterium was identified as a new strain (PE36) of Brevibacillus latersporus, which was shown via genomic analysis to contain a large number of gene clusters presumably involved in secondary metabolite biosynthesis. A scale-up culture of B. latersporus PE36 yielded three bioactive compounds that inhibited the growth of methicillin-resistant Staphylococcus aureus (basiliskamides A and B and 12-methyltetradecanoic acid). Further studies of the isolate's secondary metabolome provided both new (auripyrazine) and previously-described pyrazine-containing compounds. In addition, a new peptidic natural product (auriporcine) was purified that was determined to be composed of a polyketide unit, two L-proline residues, two D-leucine residues, one L-leucine residue, and a reduced L-phenylalanine (L-phenylalanol). An examination of the genome revealed two gene clusters that are likely responsible for generating the basiliskamides and auriporcine. These combined genomic and chemical studies confirm that new and unusual secondary metabolites can be obtained from the bacterial associates of wild mammals.